On-ice and off-ice fitness profiles of elite and u20 male ice hockey players of two different national standards - Vigh-Larsen, J. F.; Haverinen, M. T.; Panduro, J.; Ermidis, G.; Andersen, T. B.; Overgaard, K.; Krustrup, P.; Parkkari, J.; Avela, J.; Kyröläinen, H.; Mohr, M. (The Journal of Strength and Conditioning Research, 2020)
Differences in body composition and performance were investigated between elite and U20 male ice hockey players of 2 different national standards. One hundred seventy-nine players were recruited from the highest Finnish (n = 82) and Danish (n = 61) national level, as well as from 1 U20 team from Finland (n = 19) and Denmark (n = 17). Body composition and countermovement jump performance (CMJ) were measured off-ice in addition to on-ice assessments of agility, 10- and 30-m sprint performance, and endurance capacity (the maximal Yo-Yo Intermittent Recovery Level 1 Ice Hockey Test, Yo-Yo IR1-IHmax). Large differences in on-ice performances were demonstrated between Finnish and Danish elite players for agility, 10- and 30-m sprint performance (2-3%, P = 0.05), and Yo-Yo IR1-IHmax performance (15%, P = 0.05). By contrast, no differences (P > 0.05) were present between elite players for CMJ ability or body composition. However, elite players possessed more body and muscle mass than U20 players. Finally, the Finnish U20 cohort had a similar performance level as the Danish elite players and superior 10-m sprint performance, whereas the Danish U20 level was inferior to the other groups in every performance assessment (P = 0.05). In conclusion, on-ice speed and endurance differ markedly between elite players of 2 different national standards with no distinction in body composition or CMJ ability. Moreover, the most consistent difference between U20 and senior elite players was related to body and muscle mass. These results highlight the usefulness of on-ice assessments and suggest the importance of on-ice high-intensity training in elite players in addition to training targeted the development of lean body mass in youth prospects.